A natureza e a cultura no compasso de um naturalista do século XIX: Wallace e a Amazônia - ALVES, José Jerônimo de Alencar (2015)
Alfred Russel Wallace traveled through the Amazon from 1848 to 1852. His perceptions of the region were informed by his systematized knowledge but also influenced by judgments of an ethical and aesthetic nature, as was common among naturalists. He saw the region's 'natives' as peaceful and friendly but likewise susceptible to the vices of civilization. Nature afforded a privileged setting both for the activities of natural history and for aesthetic pleasures. These features helped keep the naturalist in the region, where he could thus engage in his scientific activities.